Public opinion on policy and budgetary trade-offs in European welfare states: evidence from a new comparative survey. Issue 6 (17th June 2017) - Busemeyer, Marius R.; Garritzmann, Julian L.
ABSTRACT: In the wake of the 'Great Recession', welfare states have entered a new phase of austerity. Simultaneously, new social risks and the rise of the knowledge economy fuel new demands on the welfare state. We analyse how demands for social investment policies – particularly education – come into conflict with budgetary concerns, using new survey data on individual-level preferences in eight European countries. Paying particular attention to fiscal and budgetary trade-offs, we find that social investments are generally very popular, but as soon as realistic budget constraints are added, public support drops considerably. The largest drop occurs when social investments would be financed with cutbacks in social transfers rather than higher taxes or higher public debt levels. Furthermore, when studying the determinants of preferences, we find that in the era of permanent austerity distributive conflicts within welfare states exhibit a different political dynamic than conflicts about the size of the welfare state.